Faktor-faktor yang Mempengaruhi Minat Membaca Siswa Kelas IV SD Negeri 117 Palembang - Rizky, Gea Ade; Tanzimah, Tanzimah; Syaflin, Sylvia Lara (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study was to determine the factors that influence reading interest in fourth-grade students of SD Negeri 117 Palembang. The method used in this research is the descriptive quantitative method. Data collection techniques used questionnaires, interviews, and documentation, while data analysis techniques used percentages, data reduction (data reduction), data presentation (data display),and conclusion drawing. Results Based on the research, it can be seen that the total answers to the questionnaire are 1712 and the maximum score is 2280 with a percentage of 75.09%. Thus, it can be said that the factors that influence reading interest in fourth-grade students of SD Negeri 117 Palembang based on the family environment are 75.09% in the high category. Results Based on the research, it can be seen that the total answers to the questionnaire are 1749 and the maximum score is 2280 with a percentage of 75.09%. Thus, it can be said that the factors that influence reading interest in fourth-grade students of SD Negeri 117 Palembang based on the curriculum are 76.71% in the high category. Results Based on the research, it can be seen that the total answers to the questionnaire are 1781 and the maximum score is 2280 with a percentage of 78.11%. Thus, it can be said that the factors that influence reading interest in fourth-grade students of SD Negeri 117 Palembang based on infrastructure are 78.11% in the high category.